PROFESIONALISME NADZIR DALAM PENGELOLAAN WAKAF DI MASJID AL INAYAH DUSUN MELIK DESA PARIJATAH KULON KECAMATAN SRONO KABUPATEN BANYUWANGI - Habibulloh Habibulloh; Afria Rachmawati; Yeni Rokhilawati; Gilang Ramadhan (Islamic Banking Department, Faculty of Islamic Economics and Business, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, Indonesia., 2023)
The aim of this research is to determine the professionalism of nadzir in managing waqf at the Al-Inayah Mosque, Dusun Melik, Parijatah Village, Kulon district. Banyuwangi. This research uses a qualitative approach and a phenomenological type of research, the research subject is the chairman of the takmir of the Al-Inayah mosque (nadzir waqf) and the waqf property manager (waqf section). Data collection uses observation, interviews, documentation and data validation techniques using source triangulation. The results of the research show that Nadzir's professionalism influences waqf management and has a positive effect on society. The results of this research show that in principle of professionalism, the waqf nadzir at the Al-Inayah Mosque in Melik Hamlet, Parijtah Kulon Village meets the criteria, as a professional nadzir. Namely, it has the principles: (1) Excellence and responsibility. (2) Speaking and humanistic skills. (3) Understanding of law and ethics. Keywords : Professionalism, Nadzir, Waqf